PREPARING EFL ONLINE CLASSROOM (A LITERATURE REVIEW): A PHENOMENOLOGICAL STUDY OF TEACHERS’ EXPERIENCES IN DESIGNING LESSON PLAN - Mifthahul Nurzanah (JAMBI-ENGLISH LANGUAGE TEACHING, 2022)
This is review related literature study which highlight regarding phenomena in the education field caused by the Covid-19 pandemic. This study is focused on the teachers’ experiences while designing lesson plan for online learning in the Covid-19 pandemic. This paper presents several studies related to the process of designing learning activities during the COVID-19 pandemic. The first discussion in this study is the elaboration of a theoretical framework regarding the process of designing a lesson plan amid the online learning in the covid-19 pandemic. The second discussion is about the problems faced by teachers when designing lesson plans in online learning. In addition, in this review of related literature, the researcher also provides a theoretical description of the online learning process from previous researchers which is summarized clearly and concisely. The researcher hopes that this paper can contribute and provide information to the interests of education, teachers and other education stakeholders. Keywords: Lesson Plan, Distance Learning, Emergency Curriculum.